USING NEW METHODOLOGICAL METHODS IN TEACHING ENGLISH DURING LESSONS AND INCREASING THE EFFECTIVENESS OF EDUCATION - Nosirova Xurshida Komil qizi (PEDAGOGS, 2025)
Annotation: this article covers theoretical and practical aspects of the use of modern methodological methods in teaching English. A significant increase in student motivation and language skills is justified through scientific analysis when interactive methods, multimedia technologies, communicative approach and competency-based educational principles are used in the course of the lesson. The study compared advanced foreign experiences as well as innovative approaches in the national education system.